Inovasi Metode Diklat yang Efektif dan Efisien di Pondok Pesantren Darussalam Banyuwang - Aulia Fanani, Bela; Syarofina Malik, Jilan; Rheiby Vallentina, Viola; Husain, Muhammaad (Jurnal Al-Kifayah: Ilmu Tarbiyah dan Keguruan, 2025)
Pesantren, as the oldest Islamic educational institution in Indonesia, faces the challenge of adaptation in the era of globalization and technology. Traditional passive training methods are considered less relevant to produce graduates with 21st century skills. This research aims to identify and formulate an innovative training model that integrates the value of pesantren with modern pedagogy, overcoming competency gaps, and utilizing technology. Previous studies have been minimal in exploring innovations in pesantren-specific training methods, including the effectiveness of active learning and 21st century skill development. This study uses a qualitative approach with a case study at the Darussalam Islamic Boarding School, Banyuwangi. Data collection was carried out through participatory observation, in-depth interviews with leaders and students, and documentation. Thematic data analysis was carried out with the help of NVivo, and data validation using triangulation. The results show the transformation of the training method through the integration of classical book study with thematic discussions, problem-based learning, the use of digital media, and social projects. Practice-based methods are very effective in increasing student involvement. Efficiency is achieved through the use of technology and the integration of activities. This innovation has been institutionalized through strategic documentation, showing that the Darussalam Islamic Boarding School is proactive in aligning tradition with modern needs, producing relevant and adaptive graduates